Nematode Problem in Root of Direct Sown Rice in Northeast Thailand - Anan Polthanee; Keisuke Nemato; Koou Yamazaki (Agriculture and Natural Resources, 1992)
Poor growth and development of rice seedling were observed in the farmers’ field in Amphur Banphai, Khon Kaen province, Northeastern Thailand. Rice root samples were taken to determine the root systems in relation to plant growth. Several root galls were found in the rice roots. Then, the plant roots were stored in formaline solution for 9 months, and further investigated in the laboratory using light microscopic method. Root galls formation was caused by nematode infection. Relationship between nematode age and root age was observed. Young nematode occurred in young rice root. Nematodes fed at all point along the root but were found more often around root tips and along lateral roots. Root damage was observed in both cortex and stele caused cell enlarge and collapse of cell wall, mainly within the cortex. The study demonstrated that nematodes affected plant growth by inhibiting water and nutrients absorption. Restriction of root elongation allowed the plant susceptible to drough under erratic rainfall condition. Future research is required to determine how nematodes can be controlled.